Variation between Populations in the Innate Immune Response to Vaccine Adjuvants - Kollmann, Tobias R. (Frontiers in Immunology, 2013)
The success of the WHO recommended ‘Expanded Program of Immunization’ (EPI) and similar regional or national programs has been astounding. However, infectious threats currently not covered by these programs continue to infect millions of infants around the world. Furthermore, many infants do not receive existing vaccines either on time or for the required number of doses to provide optimal protection. Nor do all infants around the world develop the same protective immune response to the same vaccine. As a result approximately 3 million infants die every year from vaccine preventable infections. To tackle these issues, new vaccines need to be developed as well as existing ones made easier to administer. This requires identification of age-optimized vaccine schedules and formulations. In order to be most effective this approach will need to take population-based differences in response to vaccines and adjuvants into account. This review summarizes what is currently known about differences between populations around the world in the innate immune response to existing as well as new and promising vaccine adjuvants.